P 131 Association between clinical depressive symptomatology and brain arousal regulation in medicated patients with major depression. Issue 10 (October 2017) - Wittekind, D.A.; Spada, J.; Franik, K.; Sander, C.; Hensch, T.; Hegerl, U.
Abstract : Background: According to the arousal regulation model of affective disorders, typical depressive symptoms like sensation avoidance and withdrawal in depression can partly be explained as an auto-regulatory attempt to counteract a tonically high brain arousal, which has repeatedly been shown in unmedicated patients with Major Depression (MDD). Brain arousal has so far not been studied in medicated MDD patients and it is unclear to what extent depressive symptomatology is associated with brain arousal regulation. The aim of this study was to compare arousal regulation in medicated MDD patients with healthy controls and to investigate the association between self-rated depressive symptomatology and brain arousal regulation. We hypothesized that despite drug treatment depressed patients would still show a hyperstable brain arousal compared to healthy controls and that depressive symptomatology will be positively associated with the stability of brain arousal regulation. Methods: Between 2006 and 2014, 130 currently depressed MDD patients treated with a Selective Serotonine Reuptake Inhibitor (SSRI) and 130 age- and sex-matched healthy controls received a 15 min resting EEG. Depressive symptomatology was assessed with the Beck Depression Inventory (BDI; self-assessment) and sleep quality and duration was measured with the "Allgemeiner Schlaffragebogen" (SF-A). Brain arousal was assessed with the Vigilance Algorithm Leipzig (VIGALL), which classifies 1-s EEG segments as one of seven EEG-vigilance sub-stages. Results: No difference in the regulation of brain arousal/wakefulness between medicated MDD patients and healthy controls was found. Also, there was neither a clear association between depression severity nor individual items of the BDI and arousal regulation. Conclusion: Our results are in line with a recent longitudinal study, showing a less stable arousal regulation in MDD patients after treatment with SSRI, suggesting a labilizing effect of SSRI on brain arousal regulation. Limitations are the retrospective design and the heterogenity of the group with respect to depression severity.